2017
DOI: 10.3390/ijms18050901
|View full text |Cite
|
Sign up to set email alerts
|

Collagenous Extracellular Matrix Biomaterials for Tissue Engineering: Lessons from the Common Sea Urchin Tissue

Abstract: Scaffolds for tissue engineering application may be made from a collagenous extracellular matrix (ECM) of connective tissues because the ECM can mimic the functions of the target tissue. The primary sources of collagenous ECM material are calf skin and bone. However, these sources are associated with the risk of having bovine spongiform encephalopathy or transmissible spongiform encephalopathy. Alternative sources for collagenous ECM materials may be derived from livestock, e.g., pigs, and from marine animals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 175 publications
(544 reference statements)
0
29
0
1
Order By: Relevance
“…Studies elsewhere have shown that small and large fibrils have distinct roles in stiff state, and only the small fibrils have a role in the disease states and hence lending to changing properties (Goh & Holmes, ), which could be the case in our medial tissues. Nonetheless, the possible role of factors apart from CF‐ED or a consequence of CF‐ED cannot be ruled out for compromised extracellular matrix of the medial tissue, based on previously described ability of metalloproteinases and their inhibitors to participate in matrix remodeling during lip fusion (Smane‐Filipova et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Studies elsewhere have shown that small and large fibrils have distinct roles in stiff state, and only the small fibrils have a role in the disease states and hence lending to changing properties (Goh & Holmes, ), which could be the case in our medial tissues. Nonetheless, the possible role of factors apart from CF‐ED or a consequence of CF‐ED cannot be ruled out for compromised extracellular matrix of the medial tissue, based on previously described ability of metalloproteinases and their inhibitors to participate in matrix remodeling during lip fusion (Smane‐Filipova et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Biomaterials not only function as a physical attachment for cells, but they also provide biochemical cues and activate the molecular signaling mechanisms that determine the fate of each individual cell in the culture. Generally, extracellular matrix (ECM) proteins such as collagen, 1,2 fibronectin, 3,4 and laminin 5 are widely utilized as biomimicking materials, as these proteins are the main interactors with cells in vivo and thus are valid candidates for use in vitro. 6 ECM proteins, which are generally produced and secreted by fibroblasts and other cell types such as epithelial cells, play significant roles in cellular growth and development in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal regenerative material should resemble the regenerated tissue both in physical structure and in chemical composition [ 13 ]. Collagen is the most abundant protein within the extracellular matrix (EMC)—a complex mixture of proteins and proteoglycans arranged in a three-dimensional structure [ 14 ].…”
Section: Introductionmentioning
confidence: 99%